Magnetic and mechanical properties of additively manufactured Alx(CoFeNi) complex concentrated alloys. (February 2023) - Chaudhary, V.; Nartu, M.S.K.K.Y.; Dasari, S.; Varahabhatla, S.M.; Sharma, A.; Radhakrishnan, M.; Mantri, S.A.; Gorsse, S.; Dahotre, N.B.; Ramanujan, R.V.; Banerjee, R.
Abstract: Varying the Al content, strongly influences the microstructure, magnetic and microhardness of additively manufactured Alx (CoFeNi) ( x  = 0, 10, 30) complex concentrated alloys (CCA). Compared to the single FCC phase of CoFeNi, the hierarchical FCC/L12 +BCC/B2 heterostructure of heat treated Al10 (CoFeNi) CCA displayed substantially improved saturation magnetization, Curie temperature and microhardness. However, there was no significant change in the properties of heat treated CoFeNi and Al30 (CoFeNi) CCA. These findings can be rationalized via thermodynamic modelling of the phase stability. We have demonstrated the feasibility of exploiting additive manufacturing for rapidly screening and developing novel high-performance alloys for next generation rotating electrical machines. Graphical abstract: Image, graphical abstract